2013
DOI: 10.1002/ajim.22279
|View full text |Cite
|
Sign up to set email alerts
|

The Strain Index andTLVforHAL: Risk of lateral epicondylitis in a prospective cohort

Abstract: JPE is associated with increased risk of LE. The SI and TLV for HAL are useful metrics for estimating JPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 64 publications
1
67
0
2
Order By: Relevance
“…Funnel plot (figure 3) and Egger's test did not suggest a major publication bias. Sensitivity analyses based on recent studies only, (18)(19)(20)(21) on studies with physical examination mandatory, (18,20,21) or on studies with observations for exposure assessment, (20,21) on studies with OR available only, (17)(18)(19) found similar results.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Funnel plot (figure 3) and Egger's test did not suggest a major publication bias. Sensitivity analyses based on recent studies only, (18)(19)(20)(21) on studies with physical examination mandatory, (18,20,21) or on studies with observations for exposure assessment, (20,21) on studies with OR available only, (17)(18)(19) found similar results.…”
Section: Resultsmentioning
confidence: 75%
“…All studies published found a significant estimation of relative risk for a positive association between combined biomechanical exposure involving wrist and/or elbow and occurrence of lateral epicondylitis, with an equivalent dose-response relationship for three of them: higher proportion of exposure or increase in duration were associated with a higher relative risk. (18,20,21) One study also found that two positive questionnaires yielded significant and higher relative risk than one positive questionnaire. (19) The overall meta-OR was significantly higher than 1 ( Figure 2): 2.6 [CI 1.9;3.5], with a low heterogeneity (Q=1.4, 5 degrees of freedom, P>0.05).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Stan zapalny w okolicy nadkłykcia bocznego kości ramiennej może wynikać z przeciążenia przyczepów mięśni prostowników nadgarstka lub nadkłykcia przyśrodkowego w następstwie przeciążenia przyczepów mięśni zginaczy nadgarstka [8].…”
Section: Przewlekłe Zapalenie Nadkłykci Kości Ramiennejunclassified